2019
DOI: 10.1007/s10822-019-00200-4
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing protein–ligand binding with chemical energy-wise decomposition (CHEWD): application to ligand binding in the kallikrein-8 S1 Site

Abstract: Kallikrein-8, a serine protease, is a target for structure-based drug design due to its therapeutic potential in treating Alzheimer's disease and is also useful as a biomarker in ovarian cancer. We present a binding assessment of ligands to kallikrein-8 using a residuewise decomposition of the binding energy. Binding of four putative inhibitors of kallikrein-8 is investigated through molecular dynamics simulation and ligand binding energy evaluation with two methods (MM/PBSA and WaterSwap). For visualization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Raza et al have shown that in comparison to the MM/PBSA analysis, the WaterSwap method identifies more residues with significant contribution to the calculated binding energies [86]. Additional insight can be obtained from the WaterSwap calculations as the binding free energy can be decomposed in terms of individual residue contributions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raza et al have shown that in comparison to the MM/PBSA analysis, the WaterSwap method identifies more residues with significant contribution to the calculated binding energies [86]. Additional insight can be obtained from the WaterSwap calculations as the binding free energy can be decomposed in terms of individual residue contributions.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to emphasize that the interaction energies calculated through this method are not directly comparable to experimental results (e.g., ΔΔ G for mutated enzymes) nor will they sum to the total binding energy; however, this type of decomposition analysis might be useful for the identification of residues that have the largest effects on the binding energy. The residue decomposition can be visualized and analyzed using the CHEWD plugin for Chimera or PyMol [86]. The residue decomposition indicates favorable and unfavorable interactions, information that is useful for lead development.…”
Section: Resultsmentioning
confidence: 99%
“…A molecular mechanics Poisson–Boltzmann surface area (MM-PBSA) approach 50 , 51 was employed to estimate the free energy of binding of the S-peptide to the different receptors ( Table S1 ). MM-PBSA calculations have emerged as an efficient and useful method to determine binding free energies, 50 , 51 and are widely used to study protein-ligand interactions in medicinal chemistry, 52 54 including in drug design for nAChRs. 55 , 56 The favourable calculated binding energies suggest stable complex formation between the S-peptide and all three nAChRs ( Table S1 ).…”
mentioning
confidence: 99%
“…The energy contribution of each residue for the complexes formed by the Zinc 69 and Zinc 70 obtained by the MM-GBSA method are shown in Figure 9. In this gure on the right side is show the residue contributions to binding energies using the plugin CHEWD [53] with Chimera software. From this, favorable interactions are at the blue of the color scale, that is, those that contribute to the stabilization of ligand into complex, while the red color represents interaction by residue with positive values and corresponds to unfavorable interactions values.…”
Section: Molecular Dynamics Analysismentioning
confidence: 99%